Combined Cytotoxic Effect of Inhibitors of Proteostasis on Human Colon Cancer Cells - Alina D. Nikotina; Snezhana A. Vladimirova; Nadezhda E. Kokoreva; Elena Y. Komarova; Nikolay D. Aksenov; Sergey Efremov; Elizaveta Leonova; Rostislav Pavlov; Viktor G. Kartsev; Zhichao Zhang; Boris A. Margulis; Irina V. Guzhova (MDPI AG, 2022)
Despite significant progress in the diagnosis and treatment of colorectal cancer, drug resistance continues to be a major limitation of therapy. In this regard, studies aimed at creating combination therapy are gaining popularity. One of the most promising adjuvants are inhibitors of the proteostasis system, chaperone machinery, and autophagy. The main HSP regulator, HSF1, is overactivated in cancer cells and autophagy sustains the survival of malignant cells. In this work, we focused on the selection of combination therapy for the treatment of rectal cancer cells obtained from patients after tumor biopsy without prior treatment. We characterized the migration, proliferation, and chaperone status in the resulting lines and also found them to be resistant to a number of drugs widely used in the clinic. However, these cells were sensitive to the autophagy inhibitor, chloroquine. For combination therapy, we used an HSF1 activity inhibitor discovered earlier in our laboratory, the cardenolide CL-43, which has already been proven as an auxiliary component of combined therapy in established cell lines. CL-43 effectively suppressed HSF1 activity and Hsp70 expression in all investigated cells. We tested the autophagy inhibitor, chloroquine, in combination with CL-43. Our results indicate that the use of an inhibitor of HSF1 activity in combination with an autophagy inhibitor results in effective cancer cell death, therefore, this therapeutic approach may be a promising treatment regimen for certain patients.